Employer Policy and Practice Toward Older Workers in Hong Kong: The Role of Shifting Intergenerational Dynamics. Issue 5 (20th October 2019) - Egdell, Valerie; Fuertes, Vanesa; Tjandra, Nathalia C; Chen, Tao
ABSTRACT: Many governments are seeking to encourage the extension of working lives to counteract potential labor market shortages that might result from population aging. Nevertheless, research shows that older workers continue to face a range of barriers to their labor market participation. However, this research has not tended to take a holistic view of the factors shaping employer policy and practice or acknowledge that older workers' experiences are embedded within broader social structures and age dynamics. This article reports on exploratory qualitative research undertaken in Hong Kong. It demonstrates how employer policy and practice toward older workers are shaped by intergenerational dynamics and by the social responsibility that employers feel toward different generations. It is argued that in order to more fully understand employer policy and practice toward older workers, an approach that acknowledges the social context and position of different age groups is required.